Mercado imobiliário, crédito e o Ciclo Real de Negócios: evidências a partir de um modelo DSGE para a economia estadunidense - Albuquerquemello, Vinícius Phillipe de (2018)
This dissertation aims to investigate the effect of real estate and credit markets on the Real Business Cycle. Specifically, we test the inclusion of housing rent for the analysis of some economic policies, for example, a change in the amount of loans granted in relation to collateral, given by Loan-to-value (LTV) parameter. In order to respond to this goal, Dynamic and Stochastic General Equilibrium (DSGE) models with characteristics of the US economy are used. As a result, it can be seen that the addition of rents highlights the effects of some shocks on economic variables, such as consumption and aggregate product. This fact is due to the introduction of the possibility of deciding between the purchase or rental of real estate and its consequences for economy. Another important finding was that the bankers’ willingness tolend becomes the second most relevant factor for the performance of the economy in the short and medium term, second only to Total Factor Productivity.